A retrospective analysis of the United States poultry industry: 1965 compared with 2010. (October 2017) - Putman, Ben; Thoma, Greg; Burek, Jasmina; Matlock, Marty
Abstract: The U.S. poultry industry requires a comprehensive understanding of the driving forces behind the changes in the environmental performance of poultry meat production in order to implement an effective sustainability strategy. This life cycle assessment (LCA) evaluates those changes over the past 45 years so that the industry can prioritize improvements to aspects of production that will have the greatest effect on the environmental impacts associated with poultry production. The LCA included material and energy flows associated with crop production and live poultry operations, beginning with one day old baby chicks in the grandparent generation, continuing through the parent generation, and ending with live market-weight broilers and culled hens at the farm gate. The results indicated that improvements in background systems and bird performance were the primary drivers behind a reduction in environmental impacts and decreased resource requirements in U.S. poultry meat production in 2010, as compared to 1965. Climate change, acidification, and eutrophication impacts associated with poultry production decreased by 36%, 29%, and 25% per 1000 kg poultry meat produced, respectively, from 1965 to 2010. Furthermore, resource-related impacts decreased in the categories of fossil energy use (39%), water depletion (58%), and agricultural land occupation (72%) per 1000 kg of poultry meat produced. This study provides the first retrospective analysis of poultry meat production in the United States, and the only U.S. poultry LCA that incorporates spent hen meat destined for human consumption and successive breeding generations into an analysis of broiler production. These methodological considerations provide greater insight into the impacts associated with U.S. poultry supply chains than was previously available, which will allow the U.S. poultry industry to make more informed decisions regarding an effective sustainability strategy and will increase publicly-available LCI data with contributions to the National Agricultural Library's LCA Commons. Highlights: LCA of 1965 and 2010 poultry production including impacts from breeding. The functional unit of 1000 kg poultry meat includes spent hens and broilers. Poultry produced in 2010 has lower emissions and requires fewer resources. Improvements driven by bird performance and crop yields. Despite lower impacts per 1000 kg, total industry impacts increased from 1965.